Interaction effects between serum 25(OH)D and CRP status on cancer related mortality in adult cancer survivors - HuanRui Zhang; BaoJun Dou; XiaoDi Sun; XiTao Chen (Scientific Reports)
Abstract Vitamin D deficiency and elevated CRP (C-reactive protein) levels are independent indicators of risk for mortality in cancer survivors; however, their combined association with mortality has not been examined. This study included adult cancer survivors from four NHANES cycles (2003–2010), utilizing a multistage survey design. CRP levels were measured using a latex-enhanced turbidimetric assay, and serum 25(OH)D levels were assessed using RIA and LC–MS/MS methods. Mortality data were linked with the National Death Index up to 2019. The restricted cubic spline model was used to explore the nonlinear associations with mortality. Kaplan–Meier analysis was used to examine survival curve differences. Cox analysis was employed to assess mortality risk after adjusting for confounding factors, and interaction analysis was conducted. Of the 1619 adult cancer survivors (56.9% female; weighted age 64.91 ± 0.44 years), 762 deaths were recorded during the 17-year follow-up. Higher CRP and lower 25(OH)D levels were associated with increased risks of all-cause and cancer mortality. Joint analysis revealed the High CRP and Low VID group had the highest all-cause (HR 2.40, 95% CI 1.82–3.17) and cancer (HR 5.23, 95% CI 3.15–8.70) mortality risk compared to Low CRP and High VID group. Additionally, a multiplicative interaction between serum 25(OH)D and CRP factors on cancer mortality was observed (P = 0.049), indicating a synergistic effect of these two factors on cancer mortality. Sex and ethnicity subgroup analyses revealed that the High CRP and Low VID group exhibits the highest risk for all-cause and cancer mortality, findings that are consistent with those observed in the overall population. In cancer survivors, an elevated risk of cancer and all-cause mortality is linked to vitamin D deficiency and elevated levels of CRP. In particular, the interaction between these factors may impact cancer survivors’ mortality related to cancers. Consequently, the risks may be significantly reduced through the use of anti-inflammatory medications as well as adequate intake of vitamin D.